2022
DOI: 10.1039/d2ay00799a
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification of nicotine salts in e-liquids by LC-MS/MS and GC-MS

Abstract: In this study, a novel approach is presented for the direct simultaneous determination of non-volatile and volatile nicotine salts via liquid chromatography/tandem mass spectroscopy (LC-MS/MS) and gas chromatography/mass spectroscopy (GC-MS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Furthermore, our results suggest that the effect of nicotinic salts on increasing DA release is positively correlated with blood and filter nicotine levels; however, the strength of the increase varies among nicotinic salts. Nicotine satisfaction is closely related to the protonated and free states of nicotine in the blood (El-Hellani et al, 2015;Talih et al, 2020), and different pH values and organic acid nicotine salts have important effects on the protonated state and stability of nicotine (Han et al, 2022b;Pennings et al, 2023). Our study found that nicotine benzoate and nicotine lactate had a greater ability to increase DA release, and the relationship between their stronger ability and the protonated and free states of nicotine requires further exploration.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, our results suggest that the effect of nicotinic salts on increasing DA release is positively correlated with blood and filter nicotine levels; however, the strength of the increase varies among nicotinic salts. Nicotine satisfaction is closely related to the protonated and free states of nicotine in the blood (El-Hellani et al, 2015;Talih et al, 2020), and different pH values and organic acid nicotine salts have important effects on the protonated state and stability of nicotine (Han et al, 2022b;Pennings et al, 2023). Our study found that nicotine benzoate and nicotine lactate had a greater ability to increase DA release, and the relationship between their stronger ability and the protonated and free states of nicotine requires further exploration.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, our results suggest that the effect of nicotinic salts on increasing DA release is positively correlated with blood and filter nicotine levels; however, the strength of the increase varies among nicotinic salts. Nicotine satisfaction is closely related to the protonated and free states of nicotine in the blood ( El-Hellani et al, 2015 ; Talih et al, 2020 ), and different pH values and organic acid nicotine salts have important effects on the protonated state and stability of nicotine ( Han et al, 2022b ; Pennings et al, 2023 ). Our study found that nicotine benzoate and nicotine lactate had a greater ability to increase DA release, and the relationship between their stronger ability and the protonated and free states of nicotine requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Eight organic acids were chosen for study (Figure ) based on commercial market relevance: benzoic acid (BA), lactic acid (LA), levulinic acid (LVA), succinic acid (SA), salicylic acid (SLA), tartaric acid (TA), malic acid (MA), and citric acid (CA). Of these, benzoic acid and lactic acid are the most commonly used in commercial products at present. ,, The unadjusted pH values for all e-liquid formulations in this study are shown in Table . For studies on radical formation from nicotine salts with different types of organic acid conjugates, e-liquids were formulated at equimolar ratios (1:1) of nicotine to acid and adjusted to neutral pH using sodium hydroxide (NaOH) when required.…”
Section: Methodsmentioning
confidence: 99%
“…pH measurements of e-liquids followed the protocols reported in previous studies. ,,, The acidity and basicity of e-cigarette solutions have also been measured with other techniques such as proton NMR and X-ray spectroscopy . The pH values discussed here do not necessarily represent absolute hydronium activity in solution .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation